Analysis of emission properties of intermixed InGaN/GaN quantum wells using a concentration-dependent interdiffusion model - ALSUNAIDI, MOHAMMAD (SPRINGER, 2019)
Intermixing phenomenon that occurs in quantum structures offers an effective way to manipulate the energy bandgap profile of emitting materials. In this paper, a numerical analysis of the concentration-dependent indium interdiffusion in InGaN/GaN quantum-disk-in-nanowires light-emitting devices is presented. The numerical model couples the concentration-dependent interdiffusion equations to Schrodinger's equation to determine the effect of intermixing process on emission properties of single and double quantum well structures. The details of the developed Finite Difference Time Domain (FDTD) solution algorithm and its stability analysis are presented. The main model parameters are calibrated using experimental data. Simulation results show that, consistent with experimental observations, longer annealing times or higher annealing temperatures result in progressive blue shifts in the eigen-energies with strong dependence on indium concentration profile. This simulation tool provides invaluable insight into the intermixing process and helps in device design procedures.
Keywords: Optical Phenomena and Photonics; ION-IMPLANTATION; INP; GA